On writing well the classic guide to writing nonfiction - Zinsser, William (New York HarperCollins, 2006)
On Writing Well has been praised for its sound advice, its clarity and the warmth of its style. It is a book for everybody who wants to learn how to write or who needs to do some writing to get through the day, as almost everybody does in the age of e-mail and the Internet.
Includes bibliographical references (p. [305]-309) and index.
Keywords: English language--Rhetoric.